Kolchozmärkte in Großstädten der südlichen Sorwjetunion.: Vom Bauernmarkt der Privatproduzenten zum innerstädtischen Handelszentrum - Stadelbauer, Jörg (ERDKUNDE, 1987)
Until the present, the private sector of Soviet agriculture retained ts great importance in supplying the population with fresh goods. These are mainly sold on kolkhoz markets, the greatest of which have become nodal points with large zones of attraction. However, the kolkhoz markets are not only the places where products of the collective farmers' private plots are offered and sold. They have developed from farmers' markets to intra-urban centres of retail trade often well integrated in the network of retail and department stores, service centres, and transport facilities. This development was made possible by the fact that the legal status of the markets has been assured and that nowadays organizations of the commission trade and even state enterprises are allowed to offer goods on the markets. Thus, in regard to fresh vegetable and fruit supply, competition arose between private price-making and state price-fixing, in order to curb speculative tendencies, which turned the kolkhoz markets into grey and even black markets. More over, the supply of the large markets comprises goods of the non-food sector (textiles, household goods) which are offered by the commission and the state retail trade organizations. In the following article, the analysis of kolkhoz markets starts from the unsatisfactory evaluation of scarce statistical data, goes on to an interpretation of town maps and comes to a more detailed study of a few examples. The central market of Ordzhonikidze (capital of the North Osetian Autonomous SSR) shows the characteristics of a centre with interregional relations in the north and south Caucasus. The market of Sochi (Black Sea coastal resort) profits by the demand coming from tourists. The market of Dushanbe (capital of the Tadzhik SSR) reveals some influences of the islamic tradition, and the central market of Ashkhabad (capital of the Turkmen SSR) represents new architectonic efforts which stress the fact that the kolkhoz market is considered a consolidated retail centre within the intra urban pattern.